(untitled) (Edumatika : Jurnal Riset Pendidikan Matematika, 2022)
The Introductory Mathematics Course is a crucial foundation for students to advance into more complex courses. However, many students still a crucial foundation for students to advance into more complex courses in this course. This study aims to analyze the level of mathematical concept understanding among students in Introductory Mathematics Course. This study utilized a descriptive qualitative approach and involved three mathematics education students from an Islamic Higher Education in Jambi, Indonesia. Each student was classified as having high, medium, and low ability based on their mathematical concept understanding test results. Furthermore, the students were interviewed to validate their test responses. The data was analyzed descriptively using the method-triangulation. The results of the study revealed that the students’ mathematical concept understanding in the Introductory Mathematics Course is, on average, in the medium category. Additionally, more effective learning methods are required to hone their ability to understand mathematical concepts.